Variations in the branching pattern of the tibial nerve in the posterior compartment of the leg - S A Premchand; W Benjamin (Wolters Kluwer Medknow Publications, 2020)
Background: Tibial nerve is the largest branch of sciatic nerve. It innervates muscles of the posterior compartment of the leg. Knowledge of the variations in motor branching pattern may help the surgeons when certain procedures are done for calf reduction and also for spastic equinus foot where selective neurectomy is required. It is also required for anesthetists for inducing neurolytic blocks. The aim of the present study was to study the variations in its branching pattern of the tibial nerve in the posterior compartment of the leg. Materials and Methods: The study was done by dissecting forty formalin-fixed lower limbs from twenty adult human cadavers. The origin of tibial nerve, variations, branching pattern, number of muscular branches and termination of the tibial nerve were studied. The level of origin of these nerves was taken in relation to the apex of head of fibula. Results: 57.5% showed that the origin was <12 cm and 42.5% were between 12 and 24 cm above the level of apex of head of fibula. The flexor hallucis longus received one branch in 70% and two branches in 30% of the specimens. Forty percent of the branches showed two or three divisions. The flexor digitorum longus received one branch in 95% and two branches in 5% of the specimens. Eighty percent of the branches of the muscle showed 2-4 divisions. 82.5% of nerve to soleus muscle had one branch and 17.5% had two branches. In 17.5% of the specimens, nerve to soleus originated from the nerve to the lateral head of gastrocnemius. Thirty percent of the branches showed 2-3 divisions. All specimens had one branch which supplied the tibialis posterior muscle and 47.5% of the branches showed 2-3 divisions. In 77.5% of the specimens, the termination occurred above the malleolar calcaneal axis. Conclusion: The flexor hallucis longus, flexor digitorum longus, and soleus muscle had one or two branches from tibial nerve. Single branch innervates tibialis posterior. Nerves to flexor hallucis longus, tibialis posterior, and the soleus had up to three divisions and nerve to flexor digitorum longus had up to four divisions.